Seminar Supervisors and Teacher Educators of Teachers of Persons with Special Needs. Final Report (Phase One) - Arnold, Daniel S.; Kentucky Univ., Lexington ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
Forty supervisors and teacher educators participated in a 2-week seminar which was conducted to develop knowledges about, understandings of, and empathy for persons with special needs. Through lectures, discussions, and other experiences, vocational education leaders were acquainted with the implications which persons with special needs present for program planning and implementation in vocational education. The report outlines the basic content and major activities of the seminar. Certain pertinent topics include: the identification of persons with special needs, psychological and sociological characteristics, special characteristics of those from urban and rural areas, the roles of guidance, teacher qualifications, teacher training, vocational education programs for those with special needs, administrative and community roles, employment opportunities, and federal acts and programs affecting those with special needs. Guidelines on characteristics of persons with special needs, teacher education programs, and programs for persons with special needs were developed during the seminar. Appendixes contain evaluation and application forms, copies of a pretest and post test, the guidelines, biographical sketches of the consultants, and a list of participants. (FP)
Sponsoring Agency: Office of Education (DHEW), Washington, DC. Bureau of Research.
Contract Number: OEG-1-7-070527-3543.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academically Handicapped; Disadvantaged; Disadvantaged Youth; Economically Disadvantaged; Individual Characteristics; Leadership Training; Program Administration; Program Descriptions; Program Development; Seminars; Supervisors; Teacher Education; Teacher Educators; Vocational Education